2017
DOI: 10.31254/jahm.2017.3406
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of caffeine in some commercial brands of tea consumed in India

Abstract: Caffeine is a common organic molecule found in many beverages such as coffee, tea, energy drinks and cola, which make the drinks addictive. Caffeine has drawn more attention due to its physiological effects beyond its stimulatory effect on central nervous system, hence it is used both recreationally and medically to reduce physical fatigue and restore mental alertness when unusual weakness or drowsiness occurs. Caffeine content in various energy drinks and beverage varies from 10 to 50 mg of caffeine per servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Notably, the R f values obtained for the tested compounds generally aligned with the R f values of the expected compounds, indicating successful separation and identification. Caffeine is the reference substance for the alkaloid group, exhibiting an R f value of 0.53 [ 50 ]. Terpineol is the reference substance for terpenoids with an R f value of 0.56 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the R f values obtained for the tested compounds generally aligned with the R f values of the expected compounds, indicating successful separation and identification. Caffeine is the reference substance for the alkaloid group, exhibiting an R f value of 0.53 [ 50 ]. Terpineol is the reference substance for terpenoids with an R f value of 0.56 [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The methanolic G. applanatum mushroom extract was used to assess DPPH free radical scavenging potential using previously described methods [4]. Different dosages (25,50,75, and 100 µg mL −1 ) of the methanolic mushroom extract combined with 1 mL of DPPH solution were kept at 28 • C for 30 min in dark. Methanol served as the blank, the control consisted of DPPH in methanol without the sample, ascorbic acid was utilized as the standard reference, and absorbance at 517 nm (Ab 517 ) was recorded.…”
Section: Antimicrobial Activity Of Methanolic G Applanatum Mushroom E...mentioning
confidence: 99%
“…Lauric acid is known to be contained in various plants such as coconut and has antibacterial effects [13]. Caffeine compounds in many plants such as tea, coffee, and other plants [14]. Therefore, it is important to carry out various secondary metabolic compounds including lauric acid and caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that peppermint infusion may contain up to 21% of its original essential oil in the raw material, while 75% is extracted from the polyphenolic content (Kapp et al, 2013). Tea, Camellia sinensis is a popular inexpensive beverage and a complex mixture of caffeine and tannins (Pradhan et al, 2017). Peppermint (Mentha) is single ingredient herbal tea, known best for the refreshing taste and strong spicy aroma and flavor using in food products, beverages, and chewing gum (Fischer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine is a colorless odorless white substance with bitter taste. It is used in the flavoring the food and it is found in tea as a stimulatory effect on central nervous system (Pradhan et al, 2017). The caffeine content in various tea samples was dependent on the type of tea whether it is black, green white, oolong or it is herbal tea.…”
Section: Introductionmentioning
confidence: 99%